Correlative microscopy of densely labeled projection neurons using neural tracers - Oberti, Daniele; Kirschmann, Moritz A.; Hahnloser, Richard (Frontiers in Neuroanatomy, 2010)
Three-dimensional morphological information about neural microcircuits is of high interest in neuroscience, but acquiring this information remains challenging. A promising new correlative technique for brain imaging is array tomography (Micheva and Smith, 2007), in which series of ultrathin brain sections are treated with fluorescent antibodies against neurotransmitters and synaptic proteins. Treated sections are repeatedly imaged in the fluorescence light microscope (FLM) and then in the electron microscope (EM). We explore a similar correlative imaging technique in which we differentially label distinct populations of projection neurons, the key routers of electrical signals in the brain. In songbirds, projection neurons can easily be labeled using neural tracers, because the vocal control areas are segregated into separate nuclei. We inject tracers into areas afferent and efferent to the main premotor area for vocal production, HVC, to retrogradely and anterogradely label different classes of projection neurons. We optimize tissue preparation protocols to achieve high fluorescence contrast in the FLM and good ultrastructure in the EM (using osmium tetroxide). Although tracer fluorescence is lost during EM preparation, we localize the tracer molecules after fixation and embedding by using fluorescent antibodies against them. We detect signals mainly in somata and dendrites, allowing us to classify synapses within a single ultrathin section as belonging to a particular type of projection neuron. The use of our method will be to provide statistical information about connectivity among different neuron classes, and to elucidate how signals in the brain are processed and routed among different areas.